Saline-Tolerant Pathogenic Acanthamoeba spp. Isolated from a Geothermal Power Plant - Elizabeth Ramírez-Flores; Patricia Bonilla-Lemus; María M. Carrasco-Yépez; Miguel A. Ramírez-Flores; Karla A. Barrón-Graciano; Saúl Rojas-Hernández; María Reyes-Batlle; Jacob Lorenzo-Morales (Pathogens, 2023)
Few studies have been conducted in the cooling systems of power plants; they have focused on Naegleria fowleri, leaving a gap in the knowledge of other pathogenic free-living amoebae in this environment. The objective of this study was to determine the occurrence of saline-tolerant pathogenic Acanthamoeba in a geothermal power plant. The identification of isolated amoebae at genus level was carried out, observing their morphological characteristics; the determination of genotype and species of Acanthamoeba was performed via molecular biology (PCR). Water temperature ranged from 18 to 43 °C and conductivity from 4.0 × 104 to 8.7 × 104 μS/cm; this last value was greater than the seawater value. Only five amoeba genera were found. Acanthamoeba was in all the sampling sites, showing high saline tolerance. The high temperature, but mainly high conductivity, were the environmental conditions that determined the presence of pathogenic free-living amoebae in the hot water. All the strains of Acanthamoeba culbertsoni killed the mice, having a mortality of 40 to 100%. Acanthamoeba genotypes T10 and T5 were identified, T10 is rarely isolated from the environment, while T5 is more frequent. This is the first time that genotypes T5 and T10 have been reported in the environment in Mexico.